Examining biomimicry-based sustainable urban design solutions from an Islamic tradition perspective / Hailane Salam ... [et al.] - Salam, Hailane; Raja Abdul Kadir, Tengku Anis Qariah; Shahbudin, Mohammad Syathir Amini; Mohd For, Liyana Mahfuzah (UiTM Press, 2024)
The study begins by examining the intersection of architecture, urban design, sustainable design, biomimicry, and Islamic tradition to understand the current landscape of sustainable urban design solutions. Identifying a critical issue related to the lack of integration between Islamic traditions and biomimicry in urban design poses significant challenges to stakeholders aiming for culturally and ecologically responsive solutions. This research departs from traditional approaches by embracing a phenomenology methodology, addressing the existing research gap concerning the alignment of sustainable design practices with Islamic values and principles. The methodology involves thematic analysis of data collected through document analysis, focusing on Malaysian architectural practices that integrate biomimicry and Islamic influences. The study is designed to systematically investigate and develop a framework that offers a more effective and innovative way to blend cultural and environmental elements in urban design, enhancing the practical application of sustainability principles within the Malaysian context. This research is expected to contribute to the understanding of sustainable urban design by providing new insights, practical frameworks, and recommendations, thereby enhancing understanding and improving practices in Malaysia.